Proposed strength and stiffness parameters for normally consolidated and overconsolidated Dhaka clay - Md. Mokhlesur, Rahman, Assoc. Prof.; Md. Abu, Taiyab; Md. Abdus, Salam; Abu Taher, Md. Zillur Rabbi; Abu, Siddique, Prof (The Institution of Engineers, Malaysia (IEM), 2013)
Link to publisher's homepage at http://www.myiem.org.my/